When Lawyers Screw Up : Improving Access to Justice for Legal Malpractice Victims - Kritzer, Herbert M., 1947-; Vidmar, Neil (Book collections on Project MUSE., 2018)
Unhappy clients bring thousands of legal malpractice claims every year, against both mega law firms and solo practitioners, for simple errors or egregious misconduct, and for losses than can reach $100 million or more. This industry, legal services, can generate nearly $300 billion a year in revenue and touches every facet of American society. Yet, scant if any scholarly attention has been paid to the questions and consequences of lawyers' professional liability. This book is the first to fully explore the mistakes lawyers sometimes make, the nature of these mistakes, the harm they do, and the significant disparities in outcomes for corporate and individual victims of lawyers' errors. A systematic, empirical study of legal malpractice, When Lawyers Screw Up employs both quantitative and qualitative methods to examine the frequency and nature of claims, the area of practice producing them, the amounts at stake, and the resolutions. The authors also use a range of data sources to study the frequency and outcomes of legal malpractice trials, whether bench or jury. Their comparison of legal malpractice cases involving the corporate and personal service sectors reveal the difficulties confronting claims coming from the personal sector--difficulties that often deny victims redress, even when they have suffered significant harm.